Pengaruh Gaya Kepemimpinan, Budaya Organisasi, dan Disiplin Kerja terhadap Kepuasan Kerja Karyawan pada KSP CU Dharma Prima Kita Yogyakarta - Oktaviani Bengan Tupen; Epsilandri Septyarini (LPPM Institut Nasional Laa Roiba Bogor, 2022)
The purpose of this study was to determine the effect of leadership style, organizational culture, and work discipline on employee job satisfaction. This study uses quantitative descriptive research methods. The population taken is the staff of KSPCU Dharma Prima Kita, the sampling method used is non-probability sampling, and the method used is saturated sampling (census). The sample consisted of 40 respondents from KSP CU Dharma Prima Kita. Methods of data collection by distributing questionnaires to respondents. Validity and reliability test, classical assumption test, descriptive test, multiple regression test, t test (partial) and f test (simultaneous) were used to prove and analyze the research results. The results showed that 1) leadership style had a positive and significant effect on job satisfaction. 2) Organizational culture has a positive and significant effect on job satisfaction. 3) Work discipline has a positive and important effect on the quality of job satisfaction. 4) Management style, organizational culture, and work discipline also have a significant positive effect on employee job satisfaction. Keywords: leadership style, organizational culture, work discipline, job satisfaction.